A novel murine model of atrial fibrillation by diphtheria toxin-induced injury - Trieu, Theresa; Mach, Philbert; Bunn, Kaitlyn; Huang, Vincent; Huang, Jamie; Chow, Christine; Nakano, Haruko; Fajardo, Viviana M.; Touma, Marlin; Ren, Shuxun; Wang, Yibin; Nakano, Atsushi (Frontiers in Physiology, 2022)
The treatment of atrial fibrillation (AF) continues to be a significant clinical challenge. While genome-wide association studies (GWAS) are beginning to identify AF susceptibility genes 1-3, non-genetic risk factors including physical, chemical, and biological environments remain the major contributors to the development of AF. However, little is known regarding how non-genetic risk factors promote the pathogenesis of AF 4-6. This is, in part, due to the lack of a robust and reliable animal model induced by non-genetic factors. The currently available models using rapid pacing protocols fail to generate a stable AF phenotype in rodent models, often requiring additional genetic modifications that introduce potential sources of bias 7. Here, we report a novel murine model of AF using an inducible and tissue-specific activation of diphtheria toxin (DT)-mediated cellular injury system. By the tissue-specific and inducible expression of human HB-EGF in atrial myocytes, we developed a reliable, robust and scalable murine model of AF that is triggered by a non-genetic inducer without the need for AF susceptibility gene mutations.